ANALISIS KINERJA KEUANGAN PASAR DAERAH: STUDI PENGEMBANGAN POTENSI MENUJU BUMD - Wahyuni, Nanik (IQTISHODUNA, 2012)
The objective of this research is to describe financial performance of traditional market on local market at Pasuruan Regency. The evaluation of financial performance based on economic principle, efficient and effectively that used to analysis development potency  to be  a region enterprise. This research used an anual financial report and management report in 2007 untill 2011. The analysis result describe that assets has owned by traditional market can be a base capital become a region enterprise of market with pay attention  increased financial performance. Based on  the evaluation value for money concluded that financial performance on traditional market  is economic, effective but inefficient.  Based on the result of financial ratio analysis conclude that traditional market at Pasuruan Regency was autonomous yet, low activity, low capital expenses,   the  growth  of expenditure  is  always higher than the growth of income,  but the equity ratio gives diskription  that traditional market can pay by self to get his assets.